Komunikasi Efektif dalam Pelaksanaan Supervisi Klinis oleh Kepala Madrasah - Tol'ah Aeni Firdiansyah (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2021)
The quality of learning is highly dependent on the quality of the teaching staff. Teachers need teaching supervision services from the head of the madrasa to overcome problems during learning, one of which is through clinical supervision. The method used in this paper uses a literature study. Clinical supervision is an effort of assistance from the head of the madrasa to help improve the professional ability of teachers in teaching through systematic stages. So far, the implementation of clinical supervision in madrasas has not fully run smoothly due to problems with harmonious communication between supervisors and teachers. Therefore, there are still many teachers who are reluctant to use clinical supervision to improve their teaching abilities. In carrying out his duties and role as a supervisor, the principal must have competencies including planning, implementing, and following up on the results of academic supervision activities for teachers by using appropriate supervision approaches and techniques, one of which maximizes effective communication. This means that the head of the madrasa as a supervisor applies two-way communication that is democratic, interactive, and produces positive feedback from the results of supervision in the form of changes in the professionalism of teaching teachers for the better. Teachers are invited to discuss and formulate what are their weaknesses in teaching, and then jointly formulate efforts to overcome them. So the head of the madrasa not only assesses but guides to seek assistance to improve the professionalism of teaching teachers. ABSTRAK Kualitas pembelajaran sangat bergantung pada kualitas dari tenaga pendidik. Guru memerlukan layanan supervisi pengajaran dari kepala madrasah untuk mengatasi permasalahan saat pembelajaran, salah satunya melalui supervisi klinis. Metode yang digunakan dalam penulisan ini menggunaan studi kepustakaan. Supervisi klinis merupakan upaya bantuan dari kepala madrasah untuk membantu meningkatkan kemampuan profesional guru dalam mengajar melalui tahapan yang sistematis. Selama ini pelaksanaan supervisi klinis di madrasah belum sepenuhnya berjalan lancar karena terkendala komunikasi yang harmonis antara supervisor dengan guru. Oleh karenannya masih banyak guru yang enggan memanfaatkan supervisi klinis untuk meningkatkan kemampuaan mengajarnya. Dalam menjalankan tugas dan perannya sebagai seorang supervisor, kepala madrasah harus memiliki kompetensi diantaranya merencanakan, melaksanakan, dan menindak lanjuti hasil kegiatan supervisi akademik terhadap guru dengan menggunakan pendekatan dan teknik supervisi yang tepat salah satunya memaksimalkan komunikasi yang efektif. Artinya kepala madrasah sebagai supervisor menerapkan komunikasi dua arah yang demokratis, interaktif, dan menghasilkan feedback positif dari hasil supervisi berupa perubahan profesionalitas mengajar guru yang lebih baik. Guru diajak berdiskusi dan merumuskan apa yang menjadi kelemahannya dalam mengajar, dan kemudian bersama-sama merumuskan upaya mengatasinya. Jadi kepala madrasah bukan hanya menilai melainkan membimbing untuk mengupayakan bantuan demi meningkatkan profesionalitas mengajar guru. Kata Kunci: Komunikasi Efektif, Supervisi Klinis dan Kepala Madrasah